Mapping the water-environment nexus for ecological sensitivity in Northern Jiangsu: Insights for sustainable ecosystem management - Liping Yin; Jiao Wu; Xingfang Qin (Desalination and Water Treatment)
This research evaluates the ecological sensitivity of Northern Jiangsu, with a focus on the relationship between water bodies and surrounding environments. By integrating water buffer zones as a core factor in sensitivity mapping, this study uses GIS and AHP methods to assess factors like vegetation and land use, revealing spatial differences in ecological vulnerability. The results highlight that areas near water bodies are more sensitive, underscoring the importance of protecting these zones to maintain ecological balance. This study not only provides a novel framework for incorporating water buffer zones into ecological sensitivity assessments but also supports policies aimed at water-related conservation and development in Northern Jiangsu.